Pengaruh Kepemilikan Manajerial, Komite Audit, dan Leverage Terhadap Integritas Laporan Keuangan dengan Kualitas Audit Sebagai Variabel Moderasi - Laeli Nur Barokah; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of managerial ownership, audit committee, and leverage on the integrity of financial statements with audit quality as a moderating variable. The research method used is a quantitative method. Manufacturing company listed on the Indonesia Stock Exchange for the 2018-2021 period were the focus of this research, which was carried out at www.idx.go.id. This research will be conducted in January 2023 until completion. Manufacturing company listed on the Indonesia Stock Exchange from 2018 to 2021 make up the study’s population. Sampling was carried out using a purposive sampling method, with predetermined criteria, in order to obtain 60  samples. The results of the study state that partially and simultaneously Managerial Ownership, Audit Committee, and Leverage have a significant effect on the Integrity of Financial Statements with Audit Quality as a Moderating Variable.Keywords: Managerial ownership, audit committee, leverage, integrity of financial statement, audit quality, and moderation variables.